Identifying the Types of Future Skills Needed in The Manufacturing Industry: A Systematic Literature Review - Kharismatul Zaenab Akhilla; Anggraini Sukmawati; Bagus Sartono (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The advent of Industrial Revolution 4.0 has led to the need to redesign the jobs and skills required across various industries and markets. As the manufacturing industry has the most significant contribution to GDP, it has not escaped the impact of this revolution. The dynamics of industrial growth, which tend to fluctuate from year to year, are also significant indicators of the need for strategic efforts to enhance the sector's resilience and competitiveness. One step that can be taken is to identify the types of future skills required and relevant to the manufacturing industry to adapt to a changing environment. Purpose: This study aims to identify the types of future skills needed by the manufacturing industry through a systematic literature review approach in order to obtain a comprehensive overview of relevant and strategic skill trends. Design/methodology/approach: This research employed the Systematic Literature Review (SLR) method, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. SLR serves as a systematic approach to identifying, evaluating, and synthesizing relevant previous research results, thereby obtaining a comprehensive understanding of the future skills required in the manufacturing industry. In addition, thematic analysis was used to identify and interpret patterns or themes within a dataset, as well as to develop a conceptual model of the study's results. Findings/Results: 63 types of future skills were categorized into eight categories. The classification of future skills in this study consists of: 1) Interpersonal Skills, 2) Leadership and Management, 3) adaptive and resilient mindsets, 4) Higher-Order Thinking Skills, 5) Entrepreneurial and Business Skills, 6) Learning and Development; Social and Ethical Responsibility; and 8) Personal Effectiveness. Conclusion: This research highlights the importance of the manufacturing industry in adapting to the changing demands brought about by Industrial Revolution 4.0 through the development of future skills. This study identified 63 types of future skills. It classifies them into eight main categories, considering the similarity of concepts, interrelationships in their application in the workplace, and the role of each skill in supporting individual readiness to face future challenges. Originality/value: This study has substantial originality value because it fills a significant research gap related to future skills in the manufacturing industry context. The lack of previous studies that specifically address future skill needs in this sector indicates the need for further exploration to strengthen the scientific foundation while making practical contributions. Therefore, this study is the first step in identifying the types of future skills that are relevant and potentially applicable to the manufacturing industry in Indonesia. Keywords: future skills, manufacturing industry, soft skills, systematic literature review, thematic analysis